Disposição a pagar pela recuperação/preservação do rio Apodi-Mossoró - Araújo, Ana Beatriz Alves de (2014)
This research aimed to identify the disposal for paying for the recovery/preservation of Apodi-Mossoró river. This purpose, accentuated by the large number of existing pollutants in the river, based on the understanding that this occurs due to the direct and indirect use of the river Apodi-Mossoró, believing in a co - participation of the entire local society. In this sense, we used a tool of neoclassical microeconomic theory, specifically of environmental economics, and among the several methods of environmental economic valuation that this theoretical branching works, opting for the use of the contingent valuation method, it is based on the revelation of consumer preferences and seeks to capture the maximum provision or reserve price, reflecting a cost-benefit analysis. Its choice was also linked to the ability to trap heat method of option and existence, by simulation of a hypothetical market, since there is no specific market for biodiversity values and environmental quality of a river. The work now composed will be developed through a dense literature review, mainly economic value of the environment since it is not trivial and therefore needs to be understood. Later, in the application of the pilot research, were made some adjustments in the questionnaire and then the final search was performed with 300 questionnaires, 150 were applied to the riverside and 150 population with the general population of the city. As tools for collecting, there were semi-structured and with easy language objective questions covering economic, social environmental data among others. The collected data were compiled and analyzed using statistical software performing multiple linear regression and applying the logit model, resulting in three demand functions for three different scenarios (general population sample, population and distant population around the river) for recovery/preservation of river Apodi-Mossoró, the observed pattern was consistent with that estimated in the three scenarios, thus validating the research. The average estimated disposal to pay by the general population was R$ 20.49. The monthly total economic value was R$ 5.323.609,35 and an annual amount of R$ 63.888.331,22. In this sense, this result confirms the preferences revealed the importance of environmental good for the city of Mossoró, which in part was willing to pay for the restoration and preservation of the natural resource population. From the learning provided by the application of the interviews was reached the following conclusion: the decision to contribute depends mainly on income, which acts as a limiting factor and decision-making, especially for the local population who had this as the main explanatory variable of willingness to fundamentador pay